Analyzing the tourism-energy-growth nexus for the top 10 most-visited countries - Cem Işik; Eyüp Doğan; Serdar Ongan (Economies, 2017)
By using the Emirmahmutoglu-Kose bootstrap Granger non-causality method, this study explores the directions of causality among tourist arrivals, tourism receipts, energy consumption and economic growth for the top 10 most-visited countries (France, the USA, Spain, China, Italy, Turkey, Germany, the United Kingdom, Russia, and Mexico) in the world. This study finds a variety of causal directions between the pair of analyzed variables for each country and the panel. Since cross-sectional dependence exists across the top countries for the analyzed variables, the bootstrap Granger causality test that accounts for the mentioned issue in the estimation process presumably produces reliable and accurate outputs. Further results and policy implications are discussed in this empirical study.
Keywords: C1; N7; O11; O13; O40; 330; Granger causality; tourist arrivals; tourism receipts; energy consumption; economic growth; the top 10 most-visited countries